Phylogeny and taxonomy of Petroschmidtia teraoi (Katayama, 1943) (Osteichthyes: Perciformes: Zoarcidae) - Nazarkin, Mikhail V.; Shinohara, Gento; Shirai, Shigeru M. (Zootaxa, 2014)
A morphological and genetic reassessment of the phylogeny and taxonomy of the dwarf zoarcid fish Lycodes teraoi Katayama, 1943 indicated that the species, a senior synonym of Lycodes sadoensis Toyoshima & Honma, 1980, should be placed in the genus Petroschmidtia. A redescription of P. teraoi is provided, with remarks on its taxonomy. Numerous specimens revealed a wide distribution of P. teraoi in the Sea of Japan, as well as in the southern Sea of Okhotsk.